Program Dukungan Organisasi dan Kesejahteraan yang Disesuaikan dengan Peran Kesehatan Dapat Meningkatkan Kepuasan Kerja dan Retensi di Klinik Kesehatan: Systematic Literature Review - Huda, Nurul; Aristawati, Evi; Cahyono, Bagus Dwi (Jurnal Keperawatan Terapan, 2025)
This systematic literature review explores the impact of organizational support and wellness programs on job satisfaction and retention among healthcare workers. Using a PRISMA-guided approach, 12 peer-reviewed studies published between 2011 and 2025 were synthesized to identify effective interventions across multiple global contexts. Key strategies include peer support programs, mindfulness training, work-life balance initiatives, relational coordination, and context-specific leadership practices. Findings reveal that perceived organizational support (POS) plays a major role in improving emotional well-being, reducing burnout, and increasing workforce retention. Contextual adaptation of programs to meet the unique needs of various professional groups—such as ICU nurses, physicians, and frontline workers in low-income settings—was found to be more effective than generic approaches. Evidence underscores the importance of integrating structural, psychosocial, and leadership-driven interventions to maintain a motivated and resilient healthcare workforce. These insights provide actionable guidance for healthcare administrators and policymakers aiming to improve employee outcomes in high-demand clinical environments.